Žinių valdymas verslo organizacijoje - Atkočiūnienė, Zenona Ona Ona (Information & Media, 2008)
Verslo organizacijai svarbią įtaką rinkoje daro žinių vadyba. Ji suteikia lankstumo, kad galėtų prisitaikyti prie aplinkos pokyčių, naujų galimybių ir jomis pasinaudotų. Šiandieninis verslas tampa informaciniu verslu, fokusuotu į organizacijos informacijos, žmonių ir technologijų išteklių organizavimą ir koordinavimą įgyvendinant organizacijos tikslus. Straipsnyje analizuojama, į ką turėtų organizacija atsižvelgti, kad žinių valdymo kryptį pasirinktų naudingai. Akcentuojama, kad verslo ir žinių vadybos veikla turėtų būti susijusi taip, kad būtų gauta maksimalios naudos suteikiant organizacijai pirmenybę ne tik į rinką, bet ir į visuomenę orientuotą verslo viziją. Knowledge control in business organization Zenona Ona Atkočiūnienė Summary Knowledge management is one of the most important inputs in the business organization control that exerts influence upon successfulness at the market, application thereof affords flexibility to organization in accommodation to environmental changes, noting some new possibilities and use them. The article stresses that business and knowledge management activities should be related in the way enabling to derive maximum profit with usage of minimal costs rendering advantage not only to the market but also to society-oriented business vision in order to direct usage and creation of knowledge in the direction that is useful for organization The article considers organization as knowledge resource and ability source, knowledge management is considered to be the ability to collect and use knowledge of staff members in order to create surplus value, increase strategy. Objective of the article is to analyze knowledge management as a summation of activities, processes, structures and means securing competitive advantage of business organization. The topic of the article is revealed pursuant to knowledge management theories and analysis of their application in the practical activity with submission of: General business organization activity and control processes in the context of creation of organizational knowledge basis; Importance of procedural knowledge control in creation of uninterrupted knowledge accumulation, organization and division environments and systems; Knowledge management estimation and usage aspects.